PENGARUH RETURN ON EQUITY DAN NET PROFIT MARGIN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN SEKTOR BATU BARA YANG TERDAFTAR DI BEI - Siti Ganiah Maulany (Universitas Muhammadiyah Bengkulu, 2024)
The purpose of this study was to determine the effect of return on equity and net profit margin on company value in the Coal Mining Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2014-2018. This research method uses a quantitative approach with multiple regression analysis. The source of this research uses secondary data sourced from the financial statements of the Coal Mining Sub Sector Company listed on the Indonesia Stock Exchange. The sample of this study was 19 companies using purposive sampling techniques. The results of this study indicate that partially Return on Equity has a significant effect on Company Value while Net Profit Margin does not have a significant effect on Firm Value. Simultaneously, the results obtained that Return on Equity and Net Profit Margin have a significant effect on Company Value, where the coefficient of determination is 0.117 shows that Return on Equity and Net Profit Margin gives a diversity of 11.7% to Firm Value, while the rest is 88.3 % is influenced by other factors not observed in this study. Keywords: Return on Equity, Net Profit Margin, Company Value